Lecture syllabus of subject Elementary Economics - Stoianova, O.E. (My University, 2014)
There is a lecture syllabus of subject Elementary Ecomonics. There are allocated four lectures- Introduction into Economics, Economizing problem, Market Demand and Supply, Private and Public sectors of the economy.
Keywords: economizing problem; demand; supply; private sector; public goods